Respostas
respondido por:
1
8 - 6x = 5
- 6x = 5 - 8
- 6x = -3........( . (-1)) ( multiplica tudo por - 1 pro x fica positivo )
x =
x =
Tirando a prova
8 - 6x = 5 tem que ser verdade.
8 - ( 6. )= 5 tem que ser verdade.
8 - 3 = 5
:)
- 6x = 5 - 8
- 6x = -3........( . (-1)) ( multiplica tudo por - 1 pro x fica positivo )
x =
x =
Tirando a prova
8 - 6x = 5 tem que ser verdade.
8 - ( 6. )= 5 tem que ser verdade.
8 - 3 = 5
:)
diegors11:
Ficou sem entender algo ?
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
10 anos atrás
10 anos atrás
10 anos atrás
10 anos atrás